Preparation, Characterization, Properties and Applications of Lead Zerconate Titanate Thin Films: A Review - et. al., Vipin Patait (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Lead Zerconate Titanate (PZT) thin film has been extensively investigated for the various important applications. Sol-gel method, chemical vapour deposition (CVD), sputtering method, pulsed laser deposition (PLD), chemical solution deposition (CSD) and ink jet method have been reviewed. Different characterization methods like X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Energy Dispersive X-Ray Analysis (EDX) and Transmission Electron Microscopy (TEM) for the as prepared PZT thin film have been studied. Important applications of PZT thin film as sensor, transducers and in MEMS has been addressed in this review. Energy harvesting applications of PZT thin film has also been focused.